Validation of individual quantitative methods for determination of cytochrome P450 probe substrates in human dried blood spots with HPLC–MS/MS. (November 2010) - Lad, Rakesh
Background: Robust individual reversed-phase HPLC–MS/MS methods have been validated for the quantitative bioanalysis of caffeine, flurbiprofen, midazolam, omeprazole and rosiglitazone in dried blood spot samples prepared from small volumes (15 µl) of human blood. Samples were punched and the resulting discs were extracted for analysis with methanol. Detection was by TurboIonSpray™ ionization combined with selected reaction monitoring MS.Results: The validated analytical concentration ranges for caffeine, flurbiprofen, midazolam, omeprazole and rosiglitazone were 250 to 25, 000 ng/ml, 100 to 10, 000 ng/ml, 0.35 to 72 ng/ml, 5 to 1000 ng/ml and 2.5 to 1000 ng/ml, respectively, and were appropriate to measure circulating concentrations for these analytes at therapeutic doses. The within-run precision and bias values for all methods were less than 15%. All compounds were stable in dried blood spots stored at room temperature and protected from moisture for at least 5 days and in whole blood for 2 h at 37°C.Conclusion: This work demonstrates that quantitative analysis of a drug extracted from dried blood spots can provide high-quality data while minimizing the volume of blood withdrawn from volunteers.